An efficient cooperative message authentication based on reputation mechanism in vehicular ad hoc networks - Yong Xie; Songsong Zhang; Xiang Li; Yanggui Li (International Journal of Distributed Sensor Networks)
Vehicular ad hoc networks have emerged as a promising approach to increasing road safety and efficiency. Vehicles periodically broadcast traffic-related status messages. Message authentication is a common way for ensuring information reliability, but it is an unaffordable computational cost for single vehicle. In this article, we propose an efficient cooperative message authentication based on reputation mechanism. In the proposed scheme, reputation model is used to assess authentication efforts of vehicles, which enhances initiative for cooperative message authentication and inhabits selfish behavior; sequence optimization algorithm solves messages overflowing on condition limited computation of onboard unit and improves the speed of message authentication at the premise of ensuring the reliability of message authentication. Simulation results show that our scheme presents a nice performance of authentication efficiency, packet loss ratio, and missing detection ratio.